The Problem of Transgender Identity in the Law of Consecrated Life - Heckel, Noach (The jurist, 2024)
In many Western countries, transgender people can change their gender and first name by simply declaring this to the state authorities. Transgender persons can be biologically clearly assigned to the male or female sex but do not feel aligned with their biological sex at the core of their consciousness. Instead, they identify with the opposite sex or neither. This phenomenon raises the question for religious orders of how to deal with the gender identity of individuals within the religious community in the future and whether transgender persons can be admitted to the order. In the Catholic Church, gender assignment is fundamentally based on biological sex. Although, as emphasized by Pope Francis, biological sex can be distinguished from psychological gender, it cannot be separated from it. According to an unpublished note from the Apostolic See from 2018, the admission of a transgender person to the novitiate or for profession is therefore not possible. If a member of a religious institute with perpetual vows confronts their transgender identity, it is up to the superior, together with the affected person, to clarify whether the transgender person can continue to live in the community or whether leaving the institute is advisable or even unavoidable. The latter is generally the case if the person decides to undergo surgical and hormonal treatment to align their body with their preferred gender. However, the admission of transgender persons as diocesan hermits is conceivable under certain conditions.